2022
DOI: 10.12688/f1000research.72982.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3% binahong (Anredera cordifolia) leaf extract gel on alveolar bone healing in post-extraction tooth socket wound in Wistar rats (Rattus norvegicus)

Abstract: Background: Binahong (Anredera cordifolia (Ten.) STEENIS) is a widely available herbal plant in Indonesia and has been intensely researched for its healing abilities due to its biological activities, but few have studied its capability in accelerating hard tissue healing in post-extraction tooth sockets. The purpose of this study was to analyse the effects of 3% binahong leaf extract gel on alveolar bone healing in post-extraction sockets in Wistar rats. Methods: In this study, 48 male Wistar rats were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…This is in inline with previous studies which stated that osteoblast cells decreased from day 14 to day 28, while osteocyte cells continued to ,so that higher numbers were obtained on day 28. 15,30 The results based on Table 2 described that on the 28 th day the wound healing process in the alveolar bone socket after tooth extraction was dominated by osteocyte cells activity. This is indicated by the fact that the number of osteocyte cells has increased compared to osteoblast cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in inline with previous studies which stated that osteoblast cells decreased from day 14 to day 28, while osteocyte cells continued to ,so that higher numbers were obtained on day 28. 15,30 The results based on Table 2 described that on the 28 th day the wound healing process in the alveolar bone socket after tooth extraction was dominated by osteocyte cells activity. This is indicated by the fact that the number of osteocyte cells has increased compared to osteoblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferative activity of osteoblast cells is an indicator of new bone formation, which reached its peak on the 14 th day and started to decreased until the 28 th day, when the osteoblasts had matured. 15,30 On the 28 th day, the osteoblast cells transformed into osteocytes. This result is shown in Figure 1B and 1D.…”
Section: Discussionmentioning
confidence: 99%
“…This research is an experimental research with pre and posttest control group design. This research was conducted by making ethanol extract and infusion of binahong leaves which would be given to male mice at doses of 35 mg/KgBW, 70 mg/KgBW and 140 mg/KgBW (Hanafiah et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Saponins suppress the growth of microbes and exhibit anti-septic properties. Hanafiah et al have demonstrated the dose-dependent action of binahong leaf extract in promoting mucosal wound healing [ 10 , 11 ].…”
Section: Reviewmentioning
confidence: 99%